1977
DOI: 10.2307/1935084
|View full text |Cite
|
Sign up to set email alerts
|

Internal Cycling of Nitrogen in Shortgrass Prairie

Abstract: Study was made of the rates at which and the routes by which nitrogen once taken up by the plant moves into litter and soil compartments and from them to new plant growth. Field mini—plots were given an initial pulse treatment with 15N, following which destructive removals were made over the next 5 growing seasons. In the year oif application, 15N moved primarily to the green herbage; 0.58 of all 15N recovered in plant materials the 1st year was in such herbage. There was late season translocation of N from ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
124
1
2

Year Published

1985
1985
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 205 publications
(139 citation statements)
references
References 16 publications
12
124
1
2
Order By: Relevance
“…After 10 yrs, 15 N recovery of the applied N decreased at both topographic positions to 85% in the footslope position and 27% in the backslope position. The earlier results of Clark (1977) and those by Delgado et al (1996b) illustrate not only the strengths of the confined-microplot technique for long-term studies, but also the power of using 15 N labeling to study % 15 N recovery, turnover rates of N in the soil organic matter, and the partitioning of N between the soil and plant material. Much was also elucidated by the use of 15 N about the long-term effect of soil texture, slope position, and grassland systems on the retention of N within this type of ecosystem.…”
Section: Native Grasses (Rangeland)mentioning
confidence: 80%
See 3 more Smart Citations
“…After 10 yrs, 15 N recovery of the applied N decreased at both topographic positions to 85% in the footslope position and 27% in the backslope position. The earlier results of Clark (1977) and those by Delgado et al (1996b) illustrate not only the strengths of the confined-microplot technique for long-term studies, but also the power of using 15 N labeling to study % 15 N recovery, turnover rates of N in the soil organic matter, and the partitioning of N between the soil and plant material. Much was also elucidated by the use of 15 N about the long-term effect of soil texture, slope position, and grassland systems on the retention of N within this type of ecosystem.…”
Section: Native Grasses (Rangeland)mentioning
confidence: 80%
“…An early and perhaps classic study of the rates and the routes by which N, once taken up by the plant, moves into litter and soil compartments pools and from them to new plant growth was reported by Clark (1977). Using 15 N tracer, and physical barriers for a study conducted in Colorado in a semiarid soil moisture regime (Soil Survey Staff 1998), 64 individual cylinders (20 cm diameter and 40 cm long) were driven to a depth of 36 cm into otherwise undisturbed shortgrass prairie.…”
Section: Native Grasses (Rangeland)mentioning
confidence: 99%
See 2 more Smart Citations
“…Warm-season perennial grasses translocate N during senescence from AG to BG biomass (Clark, 1977). For example, Heckathorn & DeLucia (1994) reported that 30% of the N was translocated BG in C 4 perennial grasses in response to drought stress.…”
Section: Introductionmentioning
confidence: 99%